Influencia de la cartera vencida en la rentabilidad de la Empresa Efac Proagro - Montece Cerezo, Mariana (2020)
The company Efac Proagro, is oriented to the distribution and commercialization of agricultural products, covers sectors of several provinces, applies advisory strategies to achieve its goals, and in the financial part it has the option of opening credits to its clients, the same as In this last semester they have presented delays in their payments, increasing the company's past due portfolio, which motivates the realization of this case study. For the development of this case study the qualitative approach is used, it is limited to observing and measuring the behavior of one variable over the other, cross-sectional, it is non-experimental because the intervening variables will not be manipulated, in addition, the logical, descriptive and explanatory historical methods to expose the findings found in the analysis of the information from the phenomenon studied, showing that the company has decreased its sales for the month of June 2020 compared to the month of January 2020, which according to The ratios indicate that it is due to the mismanagement of profitability, in addition it is also considered that the presence of the pandemic and with it the security measures have affected the marketing and collection processes, the company has shown a decrease in its profits for the month From January to June 2020, the company has not established strategies for its development with regard to the financial situation. to.